Prognosis of left ventricular noncompaction with preserved ejection fraction. (14th October 2021) - Casas, G; Limeres, J; Gutierrez-Garcia, L; La Mura, L; Guala, A; Teixido, G; Escalona, R; Gonzalez-Del-Hoyo, M; Gimeno, J R; Zorio, E; Garcia-Pavia, P; Barriales, R; et al.
Abstract: Introduction: Left ventricular noncompaction (LVNC) is a poorly defined entity with heterogeneous prognosis. LV ejection fraction (LVEF) is one of the main predictors of major adverse cardiovascular events (MACE). However, outcomes of LVNC patients with preserved LVEF (pEF) remain uncertain. Purpose: The aim of our study was to determine the incidence and predictors of MACE in LVNC patients with pEF as well as to assess the evolution of LVEF throughout follow-up. Methods: We conducted a retrospective, longitudinal, multicentre cohort study. Consecutive patients with transthoracic echocardiography (TTE) and/or cardiac magnetic resonance (CMR) diagnostic criteria for LVNC and initially pEF (LVEF≥50%) were recruited. MACE were defined as a composite of heart failure (HF), ventricular arrhythmias (VA), systemic embolisms (SE) and/or all-cause mortality. Progressive systolic dysfunction was defined as an LVEF<50% at last TTE and/or an absolute ≥10-point decrease in LVEF from first to last TTE. Lower limit of LVEF values were considered 50–53% for TTE and 50–57% for CMR, according to current recommendations. Results: A total of 305 patients from 12 centres were included from 2000 to 2018. Age was 38±19 years, 165 (54%) were men and 185 (61%) were probands. LVEF was 62±8% and 8% had late gadolinium enhancement (LGE). During a median follow-up of 4.7 (IQR 2.1–7.4) years, MACE occurred in 40 (13%) patients with an incidence rate of 2.96 (95% CI 2.17–4.04) events per 100 person-years: 8 HF, 27 VA, 3 SE and 5 deaths. LVEF by TTE (HR 0.95, 95% CI 0.90–0.99, p=0.035) and age (HR 1.02, 95% CI 1.01–1-04, p=0.04) were the only variables independently associated with the endpoint. Patients with lower limit LVEF values showed an increased risk of MACE (Figure 1). Among probands, those with family aggregation presented a higher incidence of MACE compared to nonfamilial cases (HR 2.74, p=0.043). A positive genotype was not associated. Sixty-one (21%) patients experienced progressive systolic dysfunction: 31 (11%) had an LVEF<50% and 48 (17%) an absolute ≥10-point decrease in LVEF at last follow-up. On multivariate analysis, LVEF by CMR was the only independent predictor (HR 0.96, 95% CI 0.92–0.99, p=0.031). Patients with lower limit LVEF values had an increased risk (Figure 2). In this subgroup, LGE was also associated with the endpoint (HR 3.52, p=0.011). Family aggregation was not associated, while a positive genotype correlated with lower risk (HR 0.52, p=0.029). Conclusions: Patients with left ventricular noncompaction and preserved ejection fraction carry a moderate risk of major adverse cardiovascular events and progressive systolic dysfunction. LVEF remains the main predictor of outcomes in this subgroup. Patients with lower limit LVEF values are at increased risk, probably suggesting subclinical systolic dysfunction. Therefore, they should be carefully monitored. FUNDunding Acknowledgement: Type of funding sources: None.